STRATEGY TO ACHIEVE MACROECONOMIC STABILITY IN UKRAINE - SYTNYK, LIUDMYLA; SHAKHOVALOVA, IELYZAVETA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The comprehensive analysis of domestic economy and it’s actual state undoubtedly confirms its steady transformation into a small, resource-based economy. Its also proves the absence of positive trends related to key factors for ensuring financial sustainability and attaining national security. Special attention is paid to factors in the fiscal sector (an increase in budget revenues based on economic growth as the result of changes in the volume of domestic and foreign trade, due to improvement in the financial results of enterprises and an increase in wages, as well as due to changes in direct tax receipts, and a decrease in the budget deficit); it is also analysed the debt sector (management of Ukraine’s sovereign debt); the detailed attention is given to banking sector (overcoming crisis phenomena in the banking system). Revealing the institutional problems, inefficiency of the public administration system we are justifying the implementation the number of measures in the areas of economic growth recovery, development of the internal market as the basis for sustainable growth, changes in the structure and activation of export policy. The expansion of small farming can be a trigger of the Ukrainian economy’s development. A significant part of the world’s natural resources is located in Ukraine. There is a significant increase in the number of populations worldwide, as well as an increase in soil deficiency suitable for agriculture. Since Ukraine is an agricultural country and most of its lands are suitable for the production of agricultural products – it gives it significant advantages for both self-sufficiency and economic development. Ukraine has always been and remains an agrarian country. Most of its’ lands are suitable for the growing of agricultural products and it gives Ukraine the significant self-sustaining advantages for both exponential growth and supporting of country’s economy. Small farming stays the main factor of the agrarian sector’s development, it supports the economy and helps to sustain the natural resources of Ukraine.